Infrared thermography- a study into its current capabilities and future prospects - Ali, Zain; Peng, Shaoyang; Addepalli, Sri; Zhao, Yifan (Cranfield University, 2024)
The fourth industrial revolution has brought forward a paradigm shift in the analyses and interpretation of data. Emerging technologies such as artificial intelligence, Internet of Things (IoT), and cyber physical systems have accelerated the process of concepts such as decentralised decision making, automation, and digitalisation. In the context of Non-destructive Evaluation (NDE), adopting these technologies has substantially improved the efficiency of existing techniques. Currently, Ultrasound Testing (UT) has been dubbed as the “gold standard” for Non-destructive Testing (NDT). However, a major drawback to this technique is its contact-based inspection. Infrared Thermography (IRT) on the other hand offers a non-contact non-intrusive inspection and is a growing area of interest to researchers. This paper explores the impact of infrared thermography within the maintenance industry. Firstly, the current state-of-the-art in IRT is presented followed by the limitations of the technique, the current research and knowledge gap that exists in thermographic testing. Potential solutions that can overcome the limitations are proposed. These cover specific aspects of the technique such as the working principle, mathematical modelling, data interpretation and processing, automation, and digitalisation. Finally, future prospects of the technique are briefly presented.
Keywords: infrared thermography; nondestructive testing; automation; defect detection; condition monitoring; digitalisation; artificial intelligence